The environmental LCA of steel vs HDPE car fuel tanks with varied pollution control. - Dlamini, Ndumiso G.
Purpose There has been an increasing use of plastic motor car fuel tanks in recent decades with the expected benefits of lighter weight, shape flexibility and lower cost. In this paper, the environmental life cycle assessments of mild steel and high density polyethylene (HDPE) car fuel tanks in Japan are compared for two cases, namely the current average processes (base case) and for the same processes with the maximum currently feasible pollution control technology installed. Materials and methods Primarily, data from Japan are used for a life cycle inventory analysis, followed by an impact assessment based on the Life Cycle Impact Assessment Method Based on Endpoint Modelling and five other indicators. Results and discussion Mild steel shows a notably higher inventory for resources iron, manganese, zinc, coking coal, combustion coal, dolomite, limestone; for the air pollutants nitrogen oxides (NOx) from mobile sources, PM10, sulphur dioxide, hydrocarbons; and for solid waste (slag). HDPE has a higher inventory for resources liquefied natural gas reserves, oil reserves, for the air pollutants carbon dioxide, NOx from non mobile sources and sulphur oxides. The base case environmental impact assessment results for six indicators show HDPE and steel to have similar impacts for all but one of the indicators. With pollution control, the feasible reductions in respective pollutant inventories range from 0 percent to 97 percent, while the corresponding impact assessment shows indicator values reduced by 0 percent to 29 percent, with slightly improved performance of mild steel relative to HDPE. Conclusions Accounting for a 62 year period of use and recycling for the mild steel would show a further decrease in the impact of the mild steel relative to HDPE.
Keywords: Fuel tanks; Impact assessment; Indicators; Life cycle inventory; Materials; Pollution control